Analysis of the Impact of Green Accounting Implementation on the Profitability of Pak Udin's Fried Meatball Factory in Jati Baru Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra - Siti Ramadhani Saragih; Yenni Samri Juliati Nasution; Muhammad Lathief Ilhamy Nasution (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the application of Green Accounting in waste management by Pak Udin Fried Meatball Factory located in Jati Baru Village, Pagar Merbau District, Deli Serdang Regency, North Sumatra. The main focus of this study is to assess how the application of green accounting affects operational costs and its impact on business profitability. The method used is a qualitative descriptive approach with primary data sources obtained through field observations, interviews, documentation, and direct surveys at the factory location. The results of the study indicate that the application of Green Accounting in the factory is still not optimal. Solid waste management has been carried out by utilizing the remaining production dregs as animal feed and compost. However, liquid waste has not been handled optimally due to limited facilities, namely only two inadequate reservoirs, so it has the potential to pollute the surrounding environment during heavy rain. In addition, there is no specific cost recording for the construction of waste processing facilities, which makes it difficult to assess its impact on profitability. This study provides an important contribution to enriching the literature on Green Accounting, especially in the household industry sector, and offers practical insights for small business actors in implementing environmental-based accounting.